The influence of emotional salience on gaze behavior in low and high trait empathy: an exploratory eye-tracking study. Issue 1 (2nd January 2022) - Nebi, Emine; Altmann, Tobias; Roth, Marcus
ABSTRACT: Previous studies have shown that situational factors like emotional salience are associated with higher subjective levels of state empathy. The present eye-tracking study explored whether gaze behavior varies as a function of emotional salience between individuals with low and high self-reported trait empathy. In a between-subjects design, we presented three social scene images in the context of different emotion conditions (Scene 1: neutral versus positive; Scene 2: neutral versus negative; Scene 3: positive versus negative) and assessed the dwell times of individuals with low versus high self-reported empathy (measured with the Toronto Empathy Questionnaire; TEQ). Analyses revealed that whereas low- and high-TEQ participants differed in their gaze behavior after receiving neutral information, they did not differ after receiving positive or negative information. Our preliminary results suggest that gaze behavior may be more indicative of self-reported trait empathy in situations with low emotional salience than in situations with high emotional salience.